Using technology and engineering to facilitate skill acquisition and improvements in performance - McNitt-Gray, J. L.; Sand, K.; Ramos, C.; Peterson, T.; Held, L.; Brown, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
To improve performance and facilitate sport-specific skill acquisition, the challenges encountered by the athlete during competition must be understood. Quantitative evidence used to design and motivate specific modifications in movement technique often requires systematic experimentation conducted in realistic contexts. In some cases, laboratory-based experimentation and dynamic modeling can be integrated to determine how athletes are generating the forces causing the observed movements. These approaches help us ascertain why certain factors affect performance. Results can then be used as a basis for designing skill progressions used to improve performance. Examples provided in this article illustrate how the use of technology, software, and experimental-based engineering tools has facilitated skill acquisition and improved the performance of skills essential for competition in gymnastics, track and field, basketball, and volleyball.